Comparison of microscopy techniques to visualize powdery mildew (Erysiphales) conidiophores. - Moreira, Laura Souza; Carvalho, Beatriz Murizini; Vivas, Janieli Maganha Silva; Santos, Pedro Henrique Dias; Vivas, Marcelo; Silveira, Silvaldo Felipe (Científica, 2014)
Fast techniques allowing a clear view of fungal structures, specially conidiophores, are important for accurate diagnosis and identification at the genus level of powdery mildew fungi. In this study we propose a new technique for removing cuticles of leaves with a colorless nail base (cosmetic-based cellulose acetate) and transparent adhesive tape for viewing conidiophores of powdery mildew on papaya (Carica papaya ), papayuelo (Vasconcellea goudoutiana ), and yellow ipe (Tabebuia serratifolia) leaves by light microscopy. For comparison, the traditional technique of discoloration (diaphanization) of the leaves was also tested. Phase and interference contrast microscopy and liquid montant with stains were used to improve the optical contrast. The cuticle removal technique showed to be simple and easy to use, showing more clearly the conidiophores origin and the leaf topology thus evidencing that it can be used as an auxiliary routine technique for the identification of powdery mildew fungi.